Musa balbisiana genome reveals subgenome evolution and functional divergence - Zhang, J.; Li, J.; Xu, Y.; Wang, J.; Ma, W.; Wu, Z.; Yu, L.; Yang, Y.; Liu, C.; Guo, Y.; Sun, S.; Baurens, F.C.; et al. (Springer, 2019)
Banana cultivars (Musa ssp.) are diploid, triploid and tetraploid hybrids derived from Musa acuminata and Musa balbisiana. We presented a high-quality draft genome assembly of M. balbisiana with 430 Mb (87%) assembled into 11 chromosomes. We identified that the recent divergence of M. acuminata (A-genome) and M. balbisiana (B-genome) occurred after lineage-specific whole-genome duplication, and that the B-genome may be more sensitive to the fractionation process compared to the A-genome. Homoeologous exchanges occurred frequently between A- and B-subgenomes in allopolyploids. Genomic variation within progenitors resulted in functional divergence of subgenomes. Global homoeologue expression dominance occurred between subgenomes of the allotriploid. Gene families related to ethylene biosynthesis and starch metabolism exhibited significant expansion at the pathway level and wide homoeologue expression dominance in the B-subgenome of the allotriploid. The independent origin of 1-aminocyclopropane-1-carboxylic acid oxidase (ACO) homoeologue gene pairs and tandem duplication-driven expansion of ACO genes in the B-subgenome contributed to rapid and major ethylene production post-harvest in allotriploid banana fruits. The findings of this study provide greater context for understanding fruit biology, and aid the development of tools for breeding optimal banana cultivars.